Risk factors for peripheral intravenous catheter-related phlebitis in adult patients* - Simões, Adriana Moreira Noronha; Vendramim, Patrícia; Pedreira, Mavilde Luz Gonçalves (Revista da Escola de Enfermagem da USP, 2022)
Objective: To identify risk factors for peripheral intravenous catheter-related phlebitis in adult patients. Method: This is a post hoc analysis of a randomized clinical trial, totaling 1,319 patients. Demographic and clinical variables related to therapy and phlebitis were investigated. For data analysis, frequencies, measures of central tendency and dispersion were calculated, and Pearson’s chi-square test and Fisher’s exact test were used, with logistic regression, ROC curve, and Odds Ratio calculation (95% confidence interval; 5% significance level) being implemented. Results: Of the 1,319 participants, 80 (6.1%) developed phlebitis. The following were associated with the occurrence of phlebitis: reduced mobility (p = 0.015), family history of deep vein thrombosis (p = 0.05), catheterization of veins on the back of the hand (p = 0.012), pain (p < 0.01), Amoxicillin-Potassium Clavulanate (p = 0.015), and Omeprazole Sodium (p = 0.029). Conclusion: Risk factors for phlebitis involved intrinsic and extrinsic factors to the patient, indicating preventive nursing interventions such as promoting patient mobility, not catheterizing veins in the dorsal arch of the hand, cautious infusion of risk drugs, and valuing pain complaints.